Lightweight Visualisations of COBOL Code for Supporting Migration to SOA - Van Geet, Joris; Demeyer, Serge (Electronic Communications of the EASST, 2008)
In this age of complex business landscapes, many enterprises turn to Service Oriented Architecture (SOA) for aligning their IT portfolio with their business. Because of the enormous business risk involved with replacing an enterpriseâs IT landscape, a stepwise migration to SOA is required. As a first step, they need to understand and assess the current structure of their legacy systems. Based on existing reverse engineering techniques, we provide visualisations to support this process for COBOL systems and present preliminary results of an ongoing industrial case study.